Repositioning educational research on rurality and rural education in South Africa: beyond deficit paradigms - Moletsane, Relebohile (Faculty of Education, University of the Free State, 2012)
Almost two decades after the demise of apartheid, rural communities in South Africa are still plagued by seemingly insurmountable challenges, with no change in sight for those who need it most. In spite of the many interventions that have been implemented, real transformation remains elusive. This position paper is premised on the notion that this lack of social change is due, in large part, to the dominance of research paradigms that ignore the voices of those most affected and those who are the intended beneficiaries of the interventions informed by the scholarship. Thus, the paper aims to critically reflect on the nature of rurality and to map the issues that face rural communities as well as the limitations of dominant research paradigms and their impact on social change (or lack thereof). It concludes with an exploration of the possibilities for using participatory visual methods for conducting research that makes a difference in the lives of participants and those around them.
Keywords: Rurality; Rural education; Deficit paradigms; Participatory visual methods